Rare earth element-doped high-entropy MXene hydrogen storage material and preparation method thereof

By doping rare earth elements to prepare high -entropy MXENE hydrogen storage materials, the existing MXENE hydrogen storage material nitrogen storage and dynamic performance are insufficient, and efficient and fast hydrogen suction dynamic properties are realized.

CN119330304APending Publication Date: 2025-01-21ANHUI UNIV +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411493059.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing MXene hydrogen storage materials have limitations in hydrogen storage amount, kinetic performance and cycle stability, and it is difficult to meet the needs of rapid hydrogen charging and discharging.

Method used

By doping rare earth elements, high-entropy MXene hydrogen storage materials are prepared, using the hydrophilicity of rare earth elements and the structural diversity of high-entropy alloys to optimize the electronic structure and hydrogen adsorption properties of the material.

Benefits of technology

It improves the dynamic performance of hydrogen storage capacity and hydrogen suction and release, so that the material can achieve fast charging hydrogen under mild conditions, solving the problem of slow dynamic response of traditional hydrogen storage materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005100581700000061
    Figure BDA0005100581700000061
  • Figure HDA0005100581710000011
    Figure HDA0005100581710000011
  • Figure HDA0005100581710000012
    Figure HDA0005100581710000012
Patent Text Reader

Abstract

The invention provides a rare earth element-doped high-entropy MXene hydrogen storage material and a preparation method thereof, and the material is prepared by mixing transition metal, rare earth elements, aluminum powder and carbon powder, carrying out high-temperature calcination and then carrying out etching treatment to finally prepare RE / high-entropy MXene. According to the material design, the hydrophilicity of rare earth elements and the structural diversity advantage of high-entropy alloy are combined, the hydrogen absorption and desorption performance of the MXene hydrogen storage material is improved, and the prepared material can achieve the hydrogen absorption amount of about 4.72 wt% at the temperature of 25 DEG C and the pressure of 100 bar; the invention not only provides a novel high-performance material for hydrogen energy storage, but also provides important technical support for the development of a hydrogen storage technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen storage materials, and in particular to a high-entropy MXene hydrogen storage material doped with rare earth elements and a preparation method thereof. Background Art

[0002] In the wave of global energy transformation, hydrogen energy has become increasingly prominent as an ideal clean energy carrier. Its high calorific value (142MJ / kg), clean and pollution-free combustion products, and recyclable properties make it the key to future energy development. However, the current storage and transportation technology of hydrogen is a relatively weak link in the development of hydrogen energy, and it is also a common key technology for the development of hydrogen energy. Exploring an economical and efficient way to store and transport hydrogen energy is one of the keys to the current development of hydrogen energy. High-density solid-state hydrogen storage materials and technologies are considered to be one of the key links in the economic and efficient development of hydrogen energy. Although there are many types of solid-state hydrogen storage materials, the current application and research of solid-state hydrogen storage materials are mainly based on hydrogen storage alloys. The rare earth-based, titanium-iron-manganese-based, and vanadium-based solid solution system hydrogen storage materials developed so far have problems such as large self-weight and low hydrogen storage capacity. Solid-state hydrogen storage materials with high hydrogen storage capacity have problems such as harsh dehydrogenation conditions, poor kinetic conditions, and poor cycle life, which limit their large-scale application and development.

[0003] Specifically, solid-state hydrogen storage materials based on H2 molecule dissociation chemical adsorption, such as MgH2, AlH3, and LiBH4, although theoretically have high hydrogen storage capacity, are limited in practical applications due to slow kinetics, poor cycle stability, and harsh operating conditions. These challenges stem from the high energy barrier required for the dissociation of hydrogen molecules on the surface, as well as the slow diffusion rate of hydrogen atoms inside the material and the strength of chemical bonds. In contrast, physical adsorption-type solid-state hydrogen storage materials, such as the graphene family, can provide fast hydrogen adsorption / desorption kinetics and cycle stability, but are limited by low hydrogen storage density caused by van der Waals adsorption.

[0004] In 1987, GJKubas first reported that a class of transition metal complexes can reversibly capture hydrogen by weak chemical adsorption at room temperature (Acc.Chem.Res.1988,21,120–128). This discovery opened up a new way to use the Kubas effect for hydrogen storage. In recent years, research in this field has made important progress, such as the research results of Antonelli and his team, who demonstrated a molecular sieve based on the Kubas mechanism-manganese hydride molecular sieve, which can adsorb up to 10.5wt% hydrogen at room temperature and 120bar hydrogen pressure (Energy Environ.Sci.,2019,12,1580-1591). Although it belongs to the category of chemical adsorption, the hydrogen adsorption and desorption behavior of Kubas-type materials is similar to physical adsorption, showing a linear response relationship to hydrogen pressure. This is because it represents a special adsorption mode, which is between physical adsorption and chemical bonding. During this process, partial charge transfer causes the hydrogen molecules to form a special state: the hydrogen bonds are stretched but not broken. This unique intermediate state gives the material a high hydrogen storage density while retaining the rapid kinetic characteristics of physical adsorption materials.

[0005] In this context, the present invention proposes an innovative solution to the limitations of MXene hydrogen storage materials in the prior art in terms of hydrogen storage capacity, kinetic performance and cycle stability - a high-entropy MXene hydrogen storage material doped with rare earth elements and a preparation method thereof. Rare earth elements can effectively adjust the electronic structure of the material and activate the Kubas interaction due to their unique electronic structure and rich energy levels. In addition, rare earth elements have a strong affinity for hydrogen and can form a close interaction with hydrogen at the molecular level. This effect enables hydrogen molecules to be adsorbed on the surface or inside of the material under low energy conditions, which not only improves the hydrogen storage capacity, but also optimizes the kinetic performance of hydrogen absorption and desorption, which is conducive to rapid hydrogen charging and desorption under mild conditions. At the same time, the concept of "high entropy" is introduced, and through the high-entropy alloying strategy of multiple elements, not only the composition and structural diversity of the material are enriched, but also a new material platform with comprehensive performance may be provided to further optimize the hydrogen storage performance, such as increasing the hydrogen storage density and reducing the activation energy of hydrogen absorption and desorption. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a high-entropy MXene hydrogen storage material doped with rare earth elements and a preparation method thereof, aiming to enhance the hydrogen storage performance of two-dimensional layered MXene materials by combining the strong hydrogen affinity of rare earth elements and the structural diversity advantages of high-entropy alloys.

[0007] In order to achieve the purpose, the present invention adopts the following technical scheme:

[0008] A method for preparing a high-entropy MXene hydrogen storage material doped with rare earth elements comprises the following steps:

[0009] Step 1: ball-milling the transition metal, rare earth element, aluminum powder and carbon powder to obtain a mixed powder;

[0010] Step 2: calcining the mixed powder at high temperature in a protective atmosphere to obtain a MAX precursor;

[0011] Step 3: grinding the MAX precursor, mixing it with an etching solution and performing an oil bath etching treatment;

[0012] Step 4: After the etched product is centrifuged and washed multiple times, it is dried in a vacuum drying oven to obtain a high-entropy MXene hydrogen storage material doped with rare earth elements.

[0013] Preferably, in step 1, the transition metal is any five of titanium, vanadium, chromium, zirconium, niobium, molybdenum, hafnium and tantalum.

[0014] Preferably, in step 1, the molar ratio of each of the five transition metals used is the same.

[0015] Preferably, in step 1, the rare earth element is selected from one or more elements of lanthanum, cerium, praseodymium, scandium and yttrium.

[0016] Preferably, in step 1, the molar ratio of the transition metal, rare earth element, aluminum powder and carbon powder is 3:0.1:1.1:2.

[0017] Preferably, in step 2, the protective atmosphere is argon, the high temperature calcination temperature is 1400-1600°C, and the reaction time is 2-4h.

[0018] Preferably, in step 3: the MAX precursor is ground to 300-500 mesh; the etching solution is a mixed solution of LiF and concentrated hydrochloric acid or a 49wt% HF solution, and the mass volume ratio of LiF and concentrated hydrochloric acid in the mixed solution of LiF and concentrated hydrochloric acid is 2-3g:20-30mL; the ratio of etching solution to MAX precursor is 20-30mL:1g.

[0019] Preferably, in step 3, the temperature of the oil bath is 40-80° C., the stirring rate during the etching treatment is 600 rpm, and the etching treatment time is 24-96 h;

[0020] Preferably, in step 4: the centrifugal washing speed is 5000-8000r / min, the number of centrifugal washing is greater than or equal to 5 times, and the centrifugal time for each time is 4-6min; the vacuum drying temperature is 40-60°C, and the drying time is 20-24h.

[0021] A high-entropy MXene hydrogen storage material doped with rare earth elements and a preparation method thereof provided by the present invention have the following beneficial effects:

[0022] Thanks to the atomic-level mixed disorder brought by the high-entropy structure, the high-entropy MXene material of the present invention greatly promotes the rapid diffusion and transfer of hydrogen atoms inside the material, thereby accelerating the hydrogen charging and decharging rate, solving the problem of slow kinetic response of traditional hydrogen storage materials, and making the material more suitable for application scenarios of rapid hydrogen charging and decharging.

[0023] The doping of rare earth elements can effectively adjust the surface properties and electronic structure of MXene materials. At the same time, rare earth elements have strong hydrogen affinity and can effectively attract and stabilize hydrogen molecules or hydrogen atoms on their surface or in the vicinity, thereby increasing the hydrogen storage capacity. This is crucial to improving the energy density of hydrogen storage systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The La prepared in Example 1 0.05 Ce 0.05 / Ti 0.6 V 0.6 Cr 0.6 Zr 0.6 Nb 0.6 X-ray diffraction spectrum of AlC2;

[0025] Figure 2 The La prepared in Example 1 0.05 Ce 0.05 / Ti 0.6 V 0.6 Cr 0.6 Zr 0.6 Nb 0.6 X-ray diffraction spectrum of C2 X;

[0026] Figure 3 The La prepared in Example 1 0.05 Ce 0.05 / Ti 0.6 V 0.6 Cr 0.6 Zr 0.6 Nb 0.6 AlC2( Figure 3 (a)) and La 0.05 Ce 0.05 / Ti 0.6 V 0.6 Cr 0.6 Zr 0.6 Nb 0.6 C2( Figure 3 (b) SEM image of

[0027] Figure 4The La prepared in Example 1 0.05 Ce 0.05 / Ti 0.6 V 0.6 Cr 0.6 Zr 0.6 Nb 0.6 Hydrogen absorption curve of C2 at 25°C;

[0028] Figure 5 The La prepared in Example 2 0.05 Ce 0.05 / Ti 0.6 V 0.6 Cr 0.6 Mo 0.6 Ta 0.6 Hydrogen absorption curve of C2 at 25°C;

[0029] Figure 6 The La prepared in Example 3 0.1 / Ti 0.6 V 0.6 Cr 0.6 Nb 0.6 Mo 0.6 Hydrogen absorption curve of C2 at 25°C;

[0030] Figure 7 Y prepared in Example 4 0.1 / Ti 0.6 V 0.6 Cr 0.6 Nb 0.6 Mo 0.6 Hydrogen absorption curve of C2 at 25℃.

[0031] Figure 8 This is the hydrogen absorption curve of Ti3C2 prepared in Comparative Example 1 at 25°C; DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described in detail below in conjunction with the drawings in the specific implementation manner and embodiments.

[0033] The hydrogen absorption performance of the materials prepared in the following examples is tested by the volumetric method as follows: before the test, the sample is weighed in the glove box and placed in the test device, with a mass of about 1-3g. During the test, it is necessary to first check the air tightness of the instrument to ensure the accuracy of the test results, then evacuate the internal pipeline of the hydrogen storage tester, and then quickly stabilize the temperature to the specified hydrogen absorption temperature. After the temperature stabilizes, a certain pressure of high-purity hydrogen is filled into the instrument to start the hydrogen absorption test. In the present invention, the hydrogen pressure required by the system is 100 bar, and the hydrogen absorption temperature is 25°C.

[0034] Example 1

[0035] In this embodiment, high entropy MXene hydrogen storage material doped with rare earth elements is prepared according to the following steps:

[0036] Step 1: Mix transition metals titanium, vanadium, chromium, zirconium, niobium and rare earth elements lanthanum and cerium as well as aluminum powder and carbon powder in a molar ratio of 0.6:0.6:0.6:0.6:0.6:0.05:0.05:1.1:2 by ball milling to obtain a mixed powder.

[0037] Step 2: The mixed powder was calcined at 1600°C for 3 h in an argon atmosphere to obtain La 0.05 Ce 0.05 / Ti 0.6 V 0.6 Cr 0.6 Zr 0.6 Nb 0.6 AlC precursor.

[0038] Step 3: La 0.05 Ce 0.05 / Ti 0.6 V 0.6 Cr 0.6 Zr 0.6 Nb 0.6 After grinding the AlC2 precursor to 300 mesh, take 1 g and mix it with 25 mL of 49 wt% HF etching solution and heat treat it in a 60°C oil bath for 96 h.

[0039] Step 4: After washing the etched product with ultrapure water at 8000r / min for multiple times, vacuum drying at 60℃ for 24h was obtained. 0.05 Ce 0.05 / Ti 0.6 V 0.6 Cr 0.6 Zr 0.6 Nb 0.6 C2.

[0040] The structural characteristics and hydrogen absorption performance of the material prepared in this embodiment are described below in conjunction with the accompanying drawings:

[0041] Figure 1 and Figure 3 (a) is La prepared in Example 1 0.05 Ce 0.05 / Ti 0.6 V 0.6 Cr 0.6 Zr 0.6 Nb 0.6 The X-ray diffraction spectrum and scanning electron microscopy image of AlC2 show that the MAX precursor was successfully prepared and the prepared MAX has a blocky morphology. Figure 2 and Figure 3 (b) is La prepared in Example 10.05 Ce 0.05 / Ti 0.6 V 0.6 Cr 0.6 Zr 0.6 Nb 0.6 The X-ray diffraction spectrum and scanning electron microscope image of C2 show that RE / high entropy MXene was successfully prepared, and the prepared RE / high entropy MXene has a layered morphology structure like stacked book pages. Figure 4 The La prepared in Example 1 0.05 Ce 0.05 / Ti 0.6 V 0.6 Cr 0.6 Zr 0.6 Nb 0.6 From the hydrogen absorption curve of C2 at 25°C, it can be seen that the hydrogen absorption amount of the material at 25°C and 100 bar pressure conditions is 4.72wt.%.

[0042] Example 2

[0043] In this embodiment, high entropy MXene hydrogen storage material doped with rare earth elements is prepared according to the following steps:

[0044] Step 1: Mix transition metals titanium, vanadium, chromium, molybdenum, tantalum and rare earth elements lanthanum, cerium as well as aluminum powder and carbon powder in a molar ratio of 0.6:0.6:0.6:0.6:0.6:0.05:0.05:1.1:2 by ball milling to obtain a mixed powder.

[0045] Step 2: The mixed powder was calcined at 1600°C for 4 h in an argon atmosphere to obtain La 0.05 Ce 0.05 / Ti 0.6 V 0.6 Cr 0.6 Mo 0.6 Ta 0.6 AlC2 precursor.

[0046] Step 3: La 0.05 Ce 0.05 / Ti 0.6 V 0.6 Cr 0.6 Mo 0.6 Ta 0.6 After grinding the AlC2 precursor to 300 mesh, take 1 g and mix it with 25 mL of 49 wt% HF etching solution and heat treat it in a 60°C oil bath for 96 h.

[0047] Step 4: After washing the etched product with ultrapure water at 8000r / min for multiple times, vacuum drying at 60℃ for 24h was obtained. 0.05 Ce 0.05 / Ti 0.6 V 0.6 Cr 0.6 Mo 0.6 Ta 0.6 C2.

[0048] The hydrogen absorption performance of the material prepared in this embodiment is described below in conjunction with the accompanying drawings:

[0049] Figure 5 The La prepared in Example 2 0.05 Ce 0.05 / Ti 0.6 V 0.6 Cr 0.6 Mo 0.6 Ta 0.6 From the hydrogen absorption curve of C2 at 25°C, it can be seen that the hydrogen absorption amount of the material at 25°C and 100 bar pressure conditions is 4.54wt.%.

[0050] Example 3

[0051] In this embodiment, high entropy MXene hydrogen storage material doped with rare earth elements is prepared according to the following steps:

[0052] Step 1: Mix transition metal titanium, vanadium, chromium, niobium, molybdenum and rare earth element lanthanum as well as aluminum powder and carbon powder in a molar ratio of 0.6:0.6:0.6:0.6:0.6:0.1:1.1:2 by ball milling to obtain a mixed powder.

[0053] Step 2: The mixed powder was calcined at 1600°C for 3 h in an argon atmosphere to obtain La 0.1 / Ti 0.6 V 0.6 Cr 0.6 Nb 0.6 Mo 0.6 AlC2 precursor.

[0054] Step 3: La 0.1 / Ti 0.6 V 0.6 Cr 0.6 Nb 0.6 Mo 0.6 After grinding the AlC2 precursor to 300 mesh, take 1 g and mix it with 25 mL of 49 wt% HF etching solution and heat treat it in a 60°C oil bath for 72 h.

[0055] Step 4: After washing the etched product with ultrapure water at 8000r / min for multiple times, vacuum drying at 60℃ for 24h was obtained. 0.1 / Ti 0.6 V 0.6 Cr 0.6 Nb 0.6 Mo0.6 C2.

[0056] The hydrogen absorption performance of the material prepared in this embodiment is described below in conjunction with the accompanying drawings:

[0057] Figure 6 The La prepared in Example 3 0.1 / Ti 0.6 V 0.6 Cr 0.6 Nb 0.6 Mo 0.6 From the hydrogen absorption curve of C2 at 25°C, it can be seen that the hydrogen absorption amount of the material at 25°C and 100 bar pressure conditions is 2.26wt.%.

[0058] Example 4

[0059] In this embodiment, high entropy MXene hydrogen storage material doped with rare earth elements is prepared according to the following steps:

[0060] Step 1: Mix transition metals titanium, vanadium, chromium, niobium, molybdenum and rare earth element yttrium as well as aluminum powder and carbon powder in a molar ratio of 0.6:0.6:0.6:0.6:0.6:0.1:1.1:2 by ball milling to obtain a mixed powder.

[0061] Step 2: The mixed powder was calcined at 1500°C for 4 h in an argon atmosphere to obtain Y 0.1 / Ti 0.6 V 0.6 Cr 0.6 Nb 0.6 Mo 0.6 AlC2 precursor.

[0062] Step 3: Y 0.1 / Ti 0.6 V 0.6 Cr 0.6 Nb 0.6 Mo 0.6 After grinding the AlC2 precursor to 300 mesh, take 1 g and mix it with 25 mL of 49 wt% HF etching solution and heat treat it in a 60°C oil bath for 72 h.

[0063] Step 4: After washing the etched product with ultrapure water at 8000 r / min for multiple times, vacuum drying at 60°C for 24 h was obtained. 0.1 / Ti 0.6 V 0.6 Cr 0.6 Nb 0.6 Mo 0.6 C2.

[0064] The hydrogen absorption performance of the material prepared in this embodiment is described below in conjunction with the accompanying drawings:

[0065] Figure 7 Y prepared in Example 4 0.1 / Ti 0.6 V 0.6 Cr 0.6 Nb 0.6 Mo 0.6 From the hydrogen absorption curve of C2 at 25°C, it can be seen that the hydrogen absorption amount of the material at 25°C and 100 bar pressure conditions is 2.23wt.%.

[0066] Comparative Example 1

[0067] In this comparative example, the MXene hydrogen storage material doped with rare earth elements was prepared according to the following steps:

[0068] Step 1: Mix transition metal titanium, aluminum powder and carbon powder in a molar ratio of 3:1.2:2 by ball milling to obtain a mixed powder.

[0069] Step 2: Calcine the mixed powder at 1400°C for 2 hours in an argon atmosphere to obtain a Ti3AlC2 precursor.

[0070] Step 3: After grinding the Ti3AlC2 precursor to 300 mesh, take 1 g and add 25 mL of 49 wt% HF etching solution and heat treat it in a 60°C oil bath for 24 h.

[0071] Step 4: After washing the etched product with ultrapure water by centrifugation at 8000 r / min for multiple times, the product was vacuum dried at 60°C for 24 h to obtain Ti3C2.

[0072] The hydrogen absorption performance of the material prepared in this comparative example is described below in conjunction with the accompanying drawings:

[0073] Figure 8 This is the hydrogen absorption curve of Ti3C2 prepared in Comparative Example 1 at 25°C. It can be seen that the hydrogen absorption amount of the material at 25°C and 100 bar pressure conditions is 1.78wt.%.

[0074] Table 1 is a table of hydrogen absorption data of the MXene hydrogen storage materials prepared in Examples 1-4 and Comparative Example 1 at 25°C and a pressure of 100 bar.

[0075] Table 1

[0076]

[0077] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. For those skilled in the art, it can be understood that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. The scope of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a high entropy MXene hydrogen storage material doped with rare earth elements, characterized in that: The following steps are involved: Step 1: ball-milling the transition metal, rare earth element, aluminum powder and carbon powder to obtain a mixed powder; Step 2: calcining the mixed powder at high temperature in a protective atmosphere to obtain a MAX precursor; Step 3: grinding the MAX precursor, mixing it with an etching solution and performing an oil bath etching treatment; Step 4: After multiple centrifugation and washing of the etched product, vacuum drying is performed to obtain a high-entropy MXene hydrogen storage material doped with rare earth elements.

2. The method for preparing a high entropy MXene hydrogen storage material doped with rare earth elements according to claim 1, characterized in that: In step 1, the transition metal is any five of titanium, vanadium, chromium, zirconium, niobium, molybdenum, hafnium and tantalum.

3. The method for preparing a high entropy MXene hydrogen storage material doped with rare earth elements according to claim 2, characterized in that: In step 1, the molar ratio of each of the five transition metals used is the same.

4. The method for preparing a high entropy MXene hydrogen storage material doped with rare earth elements according to claim 1, characterized in that: In step 1, the rare earth element is selected from one or more elements of lanthanum, cerium, praseodymium, scandium and yttrium.

5. The method for preparing a high entropy MXene hydrogen storage material doped with rare earth elements according to claim 1, characterized in that: In step 1, the molar ratio of the transition metal, the rare earth element, the aluminum powder and the carbon powder is 3:0.1:1.1:

2.

6. The method for preparing a high entropy MXene hydrogen storage material doped with rare earth elements according to claim 1, characterized in that: In step 2, the protective atmosphere is argon, the high temperature calcination temperature is 1400-1600° C., and the reaction time is 2-4 hours.

7. The method for preparing a high entropy MXene hydrogen storage material doped with rare earth elements according to claim 1, characterized in that: In step 3: the MAX precursor is ground to 300-500 mesh; the etching solution is a mixed solution of LiF and concentrated hydrochloric acid or a 49wt% HF solution, and the mass volume ratio of LiF and concentrated hydrochloric acid in the mixed solution of LiF and concentrated hydrochloric acid is 2-3g:20-30mL; the ratio of etching solution to MAX precursor is 20-30mL:1g.

8. The method for preparing a high entropy MXene hydrogen storage material doped with rare earth elements according to claim 1, characterized in that: In step 3, the temperature of the oil bath is 40-80° C. and the etching treatment time is 24-96 hours.

9. The method for preparing a high entropy MXene hydrogen storage material doped with rare earth elements according to claim 1, characterized in that: In step 4: the centrifugal washing speed is 5000-8000r / min, the number of centrifugal washing is greater than or equal to 5 times, and the centrifugal time for each time is 4-6min; the temperature of the vacuum drying is 40-60°C, and the drying time is 20-24h.

10. A high-entropy MXene hydrogen storage material doped with a rare earth element obtained by the preparation method according to any one of claims 1 to 9.